The “One Piece” Autologous Tuberosity Graft: A Contemporary Concept in Ridge Preservation - Ronald Younes; Carla Maria Khairallah (Case Reports in Dentistry)
Tooth extraction causes major changes to the ridge, rendering implant placement a more challenging procedure. Proper management of the socket is necessary to ensure sufficient bone and soft tissue for a successful implant-supported prosthesis. This article presents a practical approach for autologous hard and soft tissue grafting. A soft and hard tissue graft is harvested in one piece from the maxillary tuberosity and stabilized in the extraction socket.